2011
DOI: 10.1007/s10706-011-9485-y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Equations of Vertical and Radial Consolidation by Equating Degrees of Consolidation by Settlement Analysis and Dissipation of Pore Pressure

Abstract: Degree of consolidation, U, is defined in two ways: (1) by settlement analysis and (2) by dissipation of pore pressure. Equations of vertical and radial consolidations are derived by equating the above two U. The new equations are compared with the existing equations of vertical and radial consolidations. It is shown that new equation of radial consolidation is exactly same as Barron's equation of equal strain radial consolidation while in case of vertical consolidation it is similar to later part of Terzaghi'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Excess pore pressure is generated in soil when it is subjected to external loads. The water present in the soil pores is gradually discharged, leading to a reduction in excess pore pressure [24,25]. The rate at which this dissipation occurs is commonly quantified using the consolidation coefficient (C v ).…”
Section: Variation Law Of Consolidation Coefficientmentioning
confidence: 99%
“…Excess pore pressure is generated in soil when it is subjected to external loads. The water present in the soil pores is gradually discharged, leading to a reduction in excess pore pressure [24,25]. The rate at which this dissipation occurs is commonly quantified using the consolidation coefficient (C v ).…”
Section: Variation Law Of Consolidation Coefficientmentioning
confidence: 99%
“…10 and 13, it can be shown that it leads to the following experimental Eq. 32 (Tewatia 2010;Tewatia et al 2012Tewatia et al , 2013 …”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…After 60 % consolidation vertical consolidation and radial consolidation, both are linear on d-dd/dt plot (Tewatia 1998(Tewatia , 2010Tewatia et al 2007Tewatia et al , 2012Tewatia et al , 2013. Here, the lines OA and OB are the lines joining points O and A, and O and B.…”
Section: Theoretical Considerationsmentioning
confidence: 99%